Role of Organic Acids (Acetic and Citric Acids) in Enhancing Blood Parameters, Oxidative Stress Indicators, and Immune Response in Broiler - Abdul-Sada Al-Zubaidi, Alaa Faisal; Al-Gharawi, Jassim Kassim; Al-Dhalimi, Hussain Mohammed (International Journal of Aquatic Research and Environmental Studies, 2026)
The experiment was conducted at the Agricultural Research and Experiment Station, College of Agriculture, Al Muthanna University, from February 1, 2025, to March 7, 2025. 315 one-day-old, unsexed Ross 308 hybrid broiler chicks, weighing 38 grams each, were used. The chicks were randomly distributed into 7 experimental treatments, with 45 chicks per treatment and three replicates per treatment (15 chicks/replicate). The experimental treatments were as follows: T1: Control treatment with no additives. T2 and T3 add of citric acid at a concentration of 1 and 2 gm/kg of diet. T4 and T5 add of acetic acid at a concentration of 1 and 2 gm/kg of diet. T6 and T7 T6: Add of citric acid + acetic acid at a concentration of 0.5 and 1 gm/kg for each to the diet.  The results showed a significant increase (P≤0.05) in T7 on some biochemical parameters, namely albumin, globulin, and total protein concentrations in blood plasma, accompanied by a significant decrease (P≤0.05) on cholesterol, glucose, and triglyceride concentrations. A significant improvement (P≤0.05) on the concentrations of antioxidants (malondialdehyde (MDA), glutathione (GSH-px), and catalase), in treatments that included both citric and acetic acids at a concentration of 1 gm/kg of feed for each, compared to the other experimental treatments and the control treatment. The immune response, as measured by cellular immunity (DHT), the volumetric standard for antibodies against Newcastle disease (ELISA), relative weight of the Bursas gland, and Bursa index, was significantly better (P≤0.05) during the 3-5 week post-infancy period for T7 compared to the other experimental treatments and the control treatment.
Keywords: organic acids, Citric acid, Acetic acid, blood parameters, oxidative indicators, immune response, broiler.